The Correlation Between Self-Efficacy and Academic Arabic Writing Ability among Arabic Language Education Students - Ritonga, Arip Rachman; Ritonga, Murni Sari; Ritonga, Raja Doli Jaya; Siregar, Namora Pogu (Study Program of Arabic Language Teaching, 2025)
This study aims to analyze the correlation between self-efficacy and Arabic academic writing ability among students in the Arabic Language Education Study Program at several universities in Indonesia. The research is grounded in the premise that success in academic writing is not solely determined by linguistic proficiency but is also significantly influenced by psychological factors, particularly students’ self-efficacy in managing complex academic writing demands. Employing a quantitative approach with a correlational design, the study involved 41 Arabic Language Education students from various Islamic Religious Higher Education Institutions in Indonesia, specifically: UIN Sunan Kalijaga Yogyakarta, UIN Maulana Malik Ibrahim Malang, UIN Sultan Syarif Kasim Riau, UIN Imam Bonjol Padang, UIN Ar-Raniry Banda Aceh, UIN Sunan Ampel Surabaya, UIN Syekh Ali Hasan Ahmad Addary, and Universitas Muhammadiyah Yogyakarta. The research sample was selected using a cluster random sampling technique. Data were collected via a self-efficacy questionnaire focusing on Arabic academic writing skills and were subsequently analyzed using simple linear regression. The results indicate a positive and significant correlation between self-efficacy and Arabic academic writing proficiency (R = 0.808; R² = 0.654; p < 0.05). These findings demonstrate that self-efficacy accounts for 65.4% of the variance in students’ academic writing ability. Students with higher levels of self-efficacy tend to exhibit superior writing quality, particularly in terms of perseverance, self-confidence, and the accurate application of linguistic conventions. Ultimately, this study underscores the importance of integrating pedagogical strategies that prioritize the reinforcement of psychological aspects in the development of Arabic academic writing skills.